PENGARUH PROFITABILITAS, SOLVABILITAS DAN AUDIT FEE TERHADAP AUDIT REPORT LAG (Studi Empiris di Perusahaan Ekstraktif yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017 - Pesik, Iren Meiske (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
This study aims to find empirical evidence of how the effect of profitability, solvency and audit fees affects audit report lag on extractive companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. Based on the results of research and discussion that has been done, there is no significant effect between profitability and audit report lag because it is obtained the t value of -2.012 with a significant value of 0.61> 0.05. So, the profitability of a company is high or low does not affect the delivery of financial statements in a timely manner. There is a significant influence between solvency and audit report lag because it is obtained the t value of 5.646 with a significant value of 0.000 <0.05. So, the smaller the debt to the total assets generated will extend the audit report lag. There is no influence between audit fee and audit report lag because it is obtained the t value of 0.219 with a significant value of 0.830> 0.05. So, the size of the audit costs incurred by the company does not affect the audit report lag.